2023
DOI: 10.3390/diagnostics13061169
|View full text |Cite
|
Sign up to set email alerts
|

Identifying ITGB2 as a Potential Prognostic Biomarker in Ovarian Cancer

Abstract: Epithelial ovarian cancer is by far the most lethal gynecological malignancy. The exploration of promising immunomarkers to predict prognosis in ovarian cancer patients remains challenging. In our research, we carried out an integrated bioinformatic analysis of genome expressions and their immune characteristics in the ovarian cancer microenvironment with validation in different experiments. We filtrated 332 differentially expressed genes with 10 upregulated hub genes from the Gene Expression Omnibus database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Whereas lysozyme (LYZ) is an antimicrobial ligand and is involved in central macrophage function and is therefore nonspecifically and highly expressed, LILRB4 is an immune checkpoint on myeloid cells, indicating a more regulatory role. High expression of the integrin ITGB2 was previously shown to be associated with poor survival outcome [88], underscoring that high expression in TAMs is crucial. In contrast, ITGB2 is also associated with CD8+ T cells, as it encodes the beta chain of the LFA-1 protein, which has been shown to be essential in the assembly of the immune synapse or to influence lymphocyte extravasation and T-cell recruitment to the tumor and is regulated by GDF-15 [89].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas lysozyme (LYZ) is an antimicrobial ligand and is involved in central macrophage function and is therefore nonspecifically and highly expressed, LILRB4 is an immune checkpoint on myeloid cells, indicating a more regulatory role. High expression of the integrin ITGB2 was previously shown to be associated with poor survival outcome [88], underscoring that high expression in TAMs is crucial. In contrast, ITGB2 is also associated with CD8+ T cells, as it encodes the beta chain of the LFA-1 protein, which has been shown to be essential in the assembly of the immune synapse or to influence lymphocyte extravasation and T-cell recruitment to the tumor and is regulated by GDF-15 [89].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that ITGB2 is highly expressed in a number of cancers, such as colorectal cancer, renal clear-cell carcinoma, papillary thyroid cancer, and breast cancer [ 50 ]. Many studies have demonstrated that ITGB2 is overexpressed in ovarian cancer relative to normal ovarian tissue; it is linked to metastasis and poor prognosis in ovarian cancer and can be used as a prognostic immunomarker [ 51 ]. Existing ovarian cancer studies suggest that ITGB2 targeted therapy should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ciucci et al, LG tumors exhibited a lower density of tumor-infiltrating CD68+ macrophage, along with an attenuated M2-skewed (CD163+) phenotype than benign and borderline tumors [ 76 ]. In another study by Li et al, M2 macrophage infiltration is strongly correlated with ITGB2 expression in ovarian cancer patients [ 51 ]. Similarly, SPP1, which is also an important DEG in our study, was reported to be significantly correlated with infiltrating levels of CD4+ T cells, CD8+ T cells, macrophages, neutrophils, and dendritic cells [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…High expression in cancer-associated fibroblast (CAF) could promote oral squamous cell carcinoma proliferation by regulating PI3K/AKT/mTOR pathways to enhance glycolysis activity in CAFs (64). Moreover, high expression of ITGB2 was also reported to be correlated with poor prognosis in some cancers (65,66). However, ITGB2 presented with opposite functions in NSCLC.…”
Section: B C D E F G Amentioning
confidence: 99%